ANST 101 Animals and Society - Stallwood, Kim (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Animals and Society explores the ways animals are viewed by various subcultures in American society. Students explore sociological, historical, economic, philosophical, and public policy issues regarding the treatment of animals. The uses of animals in factory farming, medical research, hunting and trapping, and the entertainment industry are examined.